Сказки. Поэмы - Пушкин Александp Сеpгеевич (Хорошие книги в школе и дома, 2022)
Экземпляры: ф. 3 (20230321) / Инвентарный номер: 65376 / Цена: 234.00 / Авт.знак: П 91 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1